Population seroprotection against hepatitis a virus in Israel 18 years after introduction of inactivated vaccine into the routine childhood vaccination schedule - Galor, Inbal; Perry Markovich, Michal; Wolf, Dana; Haber, Meital; Hartal, Michael; Avramovich, Eva (Vaccine, 2020)
Vaccine against Hepatitis A virus (HAV) is part of the routine vaccination schedule in Israel since 1999. As of 2016, new recruits to the Israel Defense Forces should have been vaccinated in their childhood. This sero-survey aimed to determine immunity against HAV 18 years after childhood vaccination, and to re-evaluate the need for HAV vaccination booster upon recruitment. Two populations were studied: soldiers who were recruited during 2011–2012, who belonged to birth cohorts before childhood vaccination (BCV) was introduced; and recruits from 2017, who belonged to birth cohorts after childhood vaccination (ACV) was introduced. Data on 339 BCV recruits and 295 ACV recruits were analyzed. Seropositivity was 35% in the BCV group and 68% in the ACV group (P < 0.0001). Seropositivity rates among ACV subjects enable evaluation of the vaccination program’s impact on the population. Our findings do not support discontinuation of HAV vaccination of at risk groups until further evaluation.